Literasi Keuangan Laku Pandai sebagai Alternatif Bisnis Ibu Rumah Tangga Desa Setro - Pratomo, Gigih; Sony Kristiyanto; Matheous Tamonsang (FEB-UP Press, 2022)
Laku Pandai's financial literacy has an important role in building character and community institutions in urban and rural areas. The purpose of this social activity is for Laku Pandai literacy as an alternative business for housewives to find out the reality, advantages and financial literacy of Laku Pandai and to identify methods and optimal solutions for Laku Pandai financial literacy as an alternative business to housewives in Setro Village. Menganti District, Gresik Regency. The results show that the main housewives know the Laku Pandai program as a financial bank service product with a good literacy level and some have become Laku Pandai agents. Setro Village has the advantage of a strategic location and constraints on the amount of costs and profit sharing which are much lower than its operational costs as well as the rapid pace of development of mobile banking and financial technology. The community can form a community to improve communication from the community, village officials, academics and the bank to provide stimulus to Laku Pandai agents to improve their performance.